2000
DOI: 10.1029/1999jd901072
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory study on heterogeneous degradation of methyl chloroform (CH3CCl3) on aluminosilica clay minerals as its potential tropospheric sink

Abstract: Heterogeneous reactions of methyl chloroform (1,1,1-trichloroethane, CH3CCI3) with alminosilica clay particles were examined between 288 and 3 !3 K as a potential sink. Allophane and halloysite particles exhibited the activity to transform CH3CCI 3 to 1,1-dichloroethene (CH:=CCI•). The dependence of the reaction rate on the pretreatment, temperature, and relative humidity suggested that the reaction could proceed under environmental conditions. Illumination of light with wavelength longer than 300 nm did not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 21 publications
3
15
1
Order By: Relevance
“…3.2.3. We also found previously that the decomposition rate of CH 3 CCl 3 on clay minerals (halloysite and allophane) decreased with increasing relative humidity (Kutsuna et al, 2000a). Figure 12 shows the k 1 value and the amount of CH 2 =CCl 2 produced in a 114-min reaction at different relative humidities.…”
Section: Effects Of Relative Humiditysupporting
confidence: 73%
See 4 more Smart Citations
“…3.2.3. We also found previously that the decomposition rate of CH 3 CCl 3 on clay minerals (halloysite and allophane) decreased with increasing relative humidity (Kutsuna et al, 2000a). Figure 12 shows the k 1 value and the amount of CH 2 =CCl 2 produced in a 114-min reaction at different relative humidities.…”
Section: Effects Of Relative Humiditysupporting
confidence: 73%
“…For the montmorillonite samples, the k 1 value varied from 1 × 10 −5 to 41 × 10 −5 s −1 for 50 mg of sample. In a previous study (Kutsuna et al, 2000a), the montmorillonite sample examined showed a small value of k 1 (montmorillonite-p in Table 1), but in this study several of the montmorillonite samples exhibited much larger k 1 values. As for the illite samples examined, the k 1 value of one material (no.…”
Section: Heterogeneous Decomposition On Various Standard Clay Mineralcontrasting
confidence: 56%
See 3 more Smart Citations